Unpacking Chinese University EFL Teachers’ Unwillingness to Use Corpus in Translation Classroom Teaching - Zhang, Yu; Huang, Fang (Social Education Research, 2025)
Corpus is beneficial for promoting students’ discovery learning and deep learning in the translation teaching context. However, it remains under-utilized by university English as a Foreign Language (EFL) teachers. Understanding the reasons of EFL teachers’ reluctance to use corpus tools is essential to maximize the pedagogical potential of corpus-based instruction. Therefore, this study conducted semi-structured interviews with four EFL teachers from a prestigious foreign language university in China to explore the reasons behind. The interview data revealed that Chinese EFL teachers generally maintained positive attitudes toward corpus, but concerns emerged when they implemented corpus in translation teaching, which gradually diminished their using intentions. The most critical issue was poor facilitating conditions, including unstable Internet connections, limited teaching hours, and training support that lacked relevance and accessibility. Insufficient corpus literacy in knowledge of corpus and perceived complexity of corpus tools also posed substantial challenges. In addition, inadequate design thinking, especially in addressing diverse student learning needs, further weakened teachers’ willingness to adopt corpus in translation teaching. Lastly, concerns were raised about limited affordance of corpus tools in supporting diverse language uses, suggesting a mismatch between the tools and pedagogical needs. The findings contribute to the technology adoption literature by situating it within the corpus-based instructional context. They underscore the importance of targeted professional development for teachers and inform policy-making on resource allocation to support effective integration in language education.